BMC (Business Model Canvas) and SWOT Analysis Approach on the Development of Farmer Prosperity: A Study on Business Strategies of "Labu Madu" Enterprises - Rimbi Imadura; Maryam Qadarin; Islamiati Hidayah (Al Tijarah, 2022)
This study is aimed to seek the role of micro Enterprises Labu Madu in Banyoksah, Sampang in prospering the farmer of pumpkin with BMC approach method and SWOT analysis. This study employed descriptive qualitative with SWOT analysis and BMC approach. The data was collected through observation, interview, and documentation. The result show that SWOT analysis with BMC approach found that the best strategy of Labu Madu enterprise to improve the welfare of pumpkin farmer is SO strategies which are first; products of Labu Madu need to displayed in the stores and use other social media as marketing such as: IG, and Shopee. Second, it is necessary to add variations to the menu of processed products from honey pumpkins, and customer requests to become resellers are a chance to increase sources of income. Third, it is necessary to take part in marketing training to increase level of producing of processed Labu Madu. Fourth, it is necessary to replace more sophisticated or modern technology so that the Labu Madu production process is easier and more efficient. Fifth, apart from having an outlet, it is necessary to open a branch to increase the source of income. To ensure the welfare of pumpkin farmer, Islamic empowerment principles needs to be applied. Moreover, sharecropping contracts also necessary to be conducted with strengthen the transparency and religiosity aspect which are ease to implement in religious culture of the farmer. Furthermore, building the café an establishing with mesmerizing view also would affect to income of the enterprise which in turn would increase the income of the farmer. In connection with that, hospitality, product diversification, and customer service should be considered for future development of the company.